Organelle genomes of two Scaevola species, S. taccada and S. hainanensis, provide new insights into evolutionary divergence between Scaevola and its related species - Meng, Danni; Lu, Tianxin; He, Meng; Ren, Yuze; Fu, Mumei; Zhang, Yuxiao; Yang, Peifeng; Lin, Xinyu; Yang, Yong; Zhang, Ying; Yang, Yuchen; Jin, Xiang (Frontiers in Plant Science, 2025)
Chloroplast and mitochondrial genomes harbor crucial information that can be utilized for elucidating plant evolution and environmental adaptation. The organellar genomic characteristics of Goodeniaceae, a sister family to Asteraceae, remain unexplored. Here, using a combination of short-read and long-read sequencing technologies, we successfully assembled the complete organellar genomes of two Goodeniaceae species native to China, Scaevola taccada and S. hainanensis. Chloroplast genome collinearity analysis revealed that Scaevola expanded its genome length through inverted repeat expansion and large single copy fragment duplication, resulting in 181,022 bp (S. taccada) and 182,726 bp (S. hainanensis), ~30 kb increase compared to its related species. Mitochondrial genomes of two Scaevola species exhibit multi-ring topology, forming dual mitochondrial chromosomes of 314,251 bp (S. taccada) and 276,175 bp (S. hainanensis). Sequence variation analysis demonstrated substantial chloroplast sequence divergence (Pi = 0.45) and an increase in gene copy number within the genus. Relative synonymous codon usage (RSCU) analysis revealed that Scaevola chloroplast has a higher bias for A/U-ending codons than mitochondria, with chloroplasts RSCU values ranging from 0.32 to 1.94, whereas mitochondrial RSCU values ranging from 0.38 to 1.62. Phylogenetic analyses support the monophyly of the Asteraceae-Goodeniaceae sister group, whereas the extended evolutionary branches of Scaevola, coupled with mitochondrial collinearity analysis, indicate rapid organellar genome evolution of Scaevola. Organellar-nuclear horizontal gene transfer analysis identified specific increased in the copy numbers of photosynthesis-related genes and chloroplast-nuclear transfer events in S. taccada. Our study not only provides insights for understanding environmental adaptation mechanisms of coastal plants, but also contributes to elucidating organellar genome evolution in Scaevola and Goodeniaceae.